Hubungan Body Shaming dan Media Sosial dengan Kecemasan di MTsN Al-Istiqomah Wungu Madiun - Devita Anugrah Anggraini; Mega Arianti Putri; Fitria Yuliana (PPNI UNIMMAN, 2025)
Body shaming is the behavior of belittling or commenting negatively on someone's physical appearance, which can lead to psychological effects such as anxiety. This study aims to identify the relationship between body shaming, social media use, and anxiety among adolescents at MTsN Al-Istiqomah Wungu Madiun. The research method used is quantitative with a cross-sectional design. The sample consisted of 60 respondents aged 13 to 15 years, selected using probability sampling techniques. Data were collected using questionnaires on body shaming, social media use, and the Hamilton Anxiety Rating Scale (HARS). Data analysis was conducted using multivariate linear regression testing. The results showed a significant relationship between body shaming and anxiety (p<0.05) and between social media use and anxiety (p<0.05). The conclusion of this study is that body shaming and excessive use of social media can increase anxiety among adolescents. Therefore, it is important to provide education about the negative impacts of body shaming and social media use on adolescent mental health.